2021
DOI: 10.3390/nu13010168
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Progression of Impaired Kidney Function in Japanese Adults: A Longitudinal Analysis for the Fukushima Health Management Survey, 2011–2015

Abstract: To investigate associations between dietary patterns and the risk of impaired kidney function, we analyzed data from 14,732 participants (40–89 years) who completed the baseline diet questionnaire of The Fukushima Health Management Survey in 2011. The incidence of chronic kidney disease (CKD) (estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2 or proteinuria (≥1+ by dipstick test)) and annual changes in eGFR were assessed from 2012 to 2015. Three major dietary patterns were identified. The adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“… 32 Furthermore, regarding associations between dietary patterns and the risk of lifestyle-related diseases, a Japanese vegetable diet pattern could reduce the risk of developing dyslipidemia and CKD. 33 , 34 …”
Section: Methods and Resultsmentioning
confidence: 99%
“… 32 Furthermore, regarding associations between dietary patterns and the risk of lifestyle-related diseases, a Japanese vegetable diet pattern could reduce the risk of developing dyslipidemia and CKD. 33 , 34 …”
Section: Methods and Resultsmentioning
confidence: 99%
“…The results of a prospective population-based study indicate a signi cant inverse association between vegetable diet and the risks of renal dysfunction and also a signi cant positive association between juice dietary pattern and eGFR < 60 ml / min / 1.73 m2 or CKD [19]. A study of 432,732 European adults found that high intake vegetables was associated with higher eGFR level [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, compared to the rst quartile of the PDI, re ned grains, animal fat, meat, egg and sodium intake was decreased signi cantly in the fourth quartile. Previous studies have shown that high carbohydrate intake with energy-dense and nutrient-poor (through acute hyperglycemia) and meat diet are associated with decreased eGFR and impaired renal function [19,25,33]. As well as the high intake of cereal bre and PUFAs have been identi ed as a protective factor in reducing the incidence of CKD [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the Hisayama Study showed that vegetable-rich diets were associated with a lower dementia risk [ 105 ], while The SONIC study showed that a plant pattern diet rich in fruits and vegetables was associated with better cognitive functions among Japanese older adults [ 130 ]. Moreover, vegetable intake in the Fukushima Health Management Survey was associated with a lower risk of CKD [ 131 ].…”
Section: Components Of Lifelong Health Support 10mentioning
confidence: 99%